Innovative design and construction for foundations and substructures subject to freezing and frost : proceedings of a session sponsored by the Geo-Institute of the American Society of Civil Engineers in conjunction with the ASCE National Convention, Minneapolis, Minnesota, October 5-8, 1997 - Tan, Chia K. (Geotechnical special publication ;, 1997)
A significant design constraint for foundations and substructures which are constructed in temperate zones of the world is the provision for protecting these foundations and substructures from the harmful effects of the frost action in the soils. These papers examine the development of new design and construction methods that modify one or more of the critical elements needed for frost action to occur: water, freezing conditions, and frost susceptible soil conditions. Recent research findings are discussed, in addition to experiences involving foundations and substructures subjected to freezing and permafrost conditions.